Kata Kunci: AI, dinding kata, digital, permainan, Anak Usia Dini (AUD) Keywords: AI, Wordwall, digital, game, Early childhood (ECD) - Titik Mariyani, Titik Mariyani (Maliki Interdisciplinary Journal, 2025)
This innovation permits the presentation of personalized learning models that can alter instruction to the wants, interface, and capacities of all children. Proficiency advancement must be prepared from a youthful age. The utilize of AI in early childhood instruction is related with more consideration since this innovation can back different angles of learning that have been accomplished within the past. This ponder could be a subjective consider with a case consider strategy. In this consider, we chose a case consider approach to clarify the advancement of advanced aptitudes through early childhood Wordwall recreations. All witnesses from this think about were instructors and understudies at the Nu 02 Tuban Muslimat Ra Organized. Based on the investigate report, it depicts the utilize of lexicon divider preparing recreations to progress cognitive aptitudes in childhood. Advancement in education learning can include understanding into proficiency, not as it were through books through computerized children. So children are not effectively bored and bored, and indeed children ended up exceptionally eager when perusing the ward appear. This innovation permits the presentation of personalized learning models that can alter instruction to the wants, interface, and capacities of all children. Proficiency advancement must be prepared from a youthful age. The utilize of AI in early childhood instruction is related with more consideration since this innovation can back different angles of learning that have been accomplished within the past. This ponder could be a subjective consider with a case consider strategy. In this consider, we chose a case consider approach to clarify the advancement of advanced aptitudes through early childhood Wordwall recreations. All witnesses from this think about were instructors and understudies at the Nu 02 Tuban Muslimat Ra Organized. Based on the investigate report, it depicts the utilize of lexicon divider preparing recreations to progress cognitive aptitudes in childhood. Advancement in education learning can include understanding into proficiency, not as it were through books through computerized children. So children are not effectively bored and bored, and indeed children ended up exceptionally eager when perusing the ward appear.